Pendampingan Kajian Tafsir Ahkam Dalam Meningkatkan Pemahaman Fiqh Ibadah Sholat Pada Masyarakat Dusun Delik Desa Kesamben - Khumairoh An Nahdliyah; Nurul Indana; Nurul Lailiyah; Elysa Nurul Qomariah; Desy Naelasari; Muh. Hasyim Rosyidi (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
This community service activity aims to improve the understanding of the people of Delik Hamlet, Kesamben Village, regarding the fiqh of prayer through guidance on the Tafsir Ahkam study. The guidance is provided to address the low level of knowledge among the community regarding the legal arguments, requirements and pillars of prayer, the law of jama' for travellers, and things that invalidate prayer, so that worship can be carried out in accordance with the teachings of the Sharia. The implementation method includes lectures using the book Tafsir Ayat Hukum Ibadah dan Makanan by Muhammad Qoyyim Yaqub as the primary reference, accompanied by question-and-answer sessions and discussions to reinforce understanding. The results of the activity showed a significant increase in participants' knowledge regarding the legal basis for the obligation of prayer, the rules for congregational prayer for travellers, the invalidators of prayer, and the understanding of the differences between conditions, pillars, and Sunnah. These changes also impacted behaviour, as residents became more disciplined, consistent, and devout in performing prayer, while also being able to balance their religious obligations with economic activities. The contribution of this community service lies in strengthening religious literacy based on effective thematic exegesis for rural communities, while also fostering religious character, social cohesion, and the application of religious moderation in daily life.